Planning for Small & Ordinary Natural Urban Spaces to Enhance Mental Health & Well-being: The Psychological Health Benefits from Contact with Nature - McNally, Wren (My University, 2014)
In the face of accelerating urbanization and rising incidence of chronic illness, nature in the urban setting is a vital contributor to quality of life. This project highlights the proven, positive effects of experiences with nature on psychological health and recommends integrating nature into small, ordinary urban spaces to create a network of natural areas that provide access to a healing environment. The modest scale of this proposed intervention offers a feasible and potentially economical opportunity to create an urban environment that supports psychological well-being. Small and publically accessible spaces provide an opportunity to increase experience with nature in the urban setting while supporting the health of individuals and communities. Incremental changes lead to significant progress over time. The project proposes a framework for evaluating the quality of small, natural urban spaces and provides recommendations for incorporating such spaces into planning efforts.
Thesis (Master's)--University of Washington, 2014
Keywords: Mental health; Psychological health; Urban nature; Well-being; Urban planning; Public health; urban planning